Pengaruh Penggunaan Alat Peraga pada Materi Pokok Dimensi Tiga terhadap Hasil Belajar Matematika - Iim Marfu'ah; Siti Julaeha; Ai Solihah (SAP (Susunan Artikel Pendidikan), 2019)
If explored more deeply, there are still many cases in the world of education today. One of the cases found was the obstacle of high school students to master the 3D geometry material. On average the 3D geometry of the national exam has the least absorption compared to other material. This is because 3D geometry material is abstract. Teaching aids become one of the solutions to overcome students' difficulties in solving problems. The purpose of this study was to determine whether there was an influence on the use of teaching aids on the subject matter of the 3D geometry in class XII SMA 34 Jakarta in 2018/2019 . The research method used is experiments. Where will be compared experimental class learning outcomes with media teaching aids and control classes with conventional learning. Data collection methods are the method of documentation, testing and observation. The prerequisite tests used were the normality test with the chi-square test, the homogeneity test and the average difference test using the t-test. From the results of the final calculation after being given an action, it is obtained ? ???? = 2,129  and ?????? = 1.991. Because ? ????> ??????, ?0 is rejected, meaning that the average learning outcomes of the experimental group are greater than the average learning outcomes of the control group.